Analisis faktor kurangnya minat belajar matematika di MTs Almaarif 03 Singosari - Primrose, Ailsa Tsabita (Maliki Interdisciplinary Journal, 2024)
This study aims to analyze the low interest in learning mathematics at MTs Almaarif 03 Singosari. As a student undergoing teaching assistance, the author conducted observations and interviews with teachers and students to understand the factors influencing this lack of interest. Findings indicate that the low interest in learning is caused by several main factors, including less varied teaching methods, lack of intrinsic motivation among students, and limited facilities and support infrastructure. Additionally, students' negative perception of mathematics as a difficult subject also contributes to this issue. This study provides recommendations for enhancing interest in learning through updating teaching methods, increasing motivational support, and improving learning facilities.